Elastomer composites containing ionic liquids - Maciejewska, M.; Krzywania-Kaliszewska, A.; Zaborski, M. (Polimery, 2015)
Ionic liquids (ILs), such as benzylimidazolium, alkylpyrrolidinium, alkylpyridinium and alkylpiperidinium salts, were applied to improve the degree of dispersion of vulcanization activator nanoparticles (zinc oxide) and silica filler in butadiene-styrene elastomer (SBR). In order to reduce the amount of zinc oxide in rubber products, nanosized zinc oxide was used instead of traditional microsized ZnO activator. It was found that the addition of ILs to rubber compounds allowed the formation of homogenous dispersion of nanoparticles in SBR, resulting in a shortened vulcanization time and decreased vulcanization temperature as well as increased crosslink density, thermal stability and resistance to UV ageing compared to traditional vulcanizates. Moreover, the amount of zinc oxide in rubber compounds was reduced by 60 % in comparison with reference samples containing micrometer-sized ZnO.